Top-Down and Bottom-Up Approach: Tinjauan Terhadap Isu Ketidakamanan Pangan Sudan Selatan - Marria Quenni Michaella; Imam Fadhil Nugraha (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Food insecurity in South Sudan represents a complex humanitarian crisis shaped by conflict, economic instability, and climate shocks, as well as the dynamics of power within humanitarian governance. This study examines the interaction between top-down and bottom-up approaches through the lens of human security using a qualitative explanatory method based on literature analysis. The findings show that top-down approaches, led by international organizations, are essential in delivering emergency aid and stabilizing short-term conditions. However, these interventions often rely on technocratic and universal frameworks that overlook local contexts, creating dependency and limiting long-term sustainability. In contrast, bottom-up approaches demonstrate that local communities are active agents who develop survival strategies through traditional agriculture, social networks, and livelihood diversification, despite facing resource constraints. This study argues that food insecurity in South Sudan is not merely a technical problem but a product of unequal power relations between global and local actors. By integrating both approaches within a human security framework, this research highlights the need to align international interventions with local realities. Sustainable solutions therefore require not only policy coordination but also greater local participation and a rebalancing of power in humanitarian governance.